Hematologic Manifestations in Celiac Disease—A Practical Review - Daniel Vasile Balaban; Alina Popp; Florentina Ionita Radu; Mariana Jinga (Medicina, 2019)
Celiac disease (CD) is a systemic autoimmune disease driven by gluten-ingestion in genetically predisposed individuals. Although it primarily affects the small bowel, CD can also involve other organs and manifest as an extraintestinal disease. Among the extraintestinal features of CD, hematologic ones are rather frequent and consist of anemia, thrombocytosis (thrombocytopenia also, but rare), thrombotic or hemorrhagic events, IgA deficiency, hyposplenism, and lymphoma. These hematologic alterations can be the sole manifestation of the disease and should prompt for CD testing in a suggestive clinical scenario. Recognition of these atypical, extraintestinal presentations, including hematologic ones, could represent a great opportunity to increase the diagnostic rate of CD, which is currently one of the most underdiagnosed chronic digestive disorders worldwide. In this review, we summarize recent evidence regarding the hematological manifestations of CD, with focus on practical recommendations for clinicians.